Effect of phenotypic detection of circulating tumor cells marked by epithelial-mesenchymal transformation on the prognosis of lung cancer: A protocol for systematic review and meta-analysis. Issue 44 (30th October 2020) - Ge, Bin; Wang, Yong; Lei, Shaoqing; Zhang, Jincao
Abstract: Background: To explore the significance of phenotype detection of circulating tumor cells (CTCs) based on epithelial-mesenchymal transition (EMT) labeling to evaluate the prognosis of lung cancer. Methods: Database was retrieved from China National Knowledge Infrastructure (CNKI), Chinese Biomedical literature Database (CBM), Chinese Scientific and Journal Database (VIP), Wan Fang database, PubMed, and EMBASE. Based on EMT on overall survival (OS) and disease-free survival (DFS), hazard ratios (HRs) and its 95% of confidence intervals (CIs) were applied to assess the prognostic effect of CTCs. RevMan 5.3 and STATA 16.0 software were adopted to perform the meta-analysis. Results: Based on EMT in terms of the prognosis of patients suffering from lung cancer, this study comprehensively reviewed and evaluated the available evidence of phenotype detection of CTCs. Conclusion: Based on EMT in the prognosis of patients who developed with lung cancer, our findings proved the effect of phenotype detection of CTCs. Such studies may reveal a new prognostic marker for lung cancer patients and help clinicians and health professionals make clinical decisions. OSF Registration Number: DOI 10.17605/OSF.IO/E7KAZ.